2022
DOI: 10.1002/jcph.2178
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin's Role in the Prevention of COVID‐19: A Systematic Review and Meta‐Analysis

Abstract: This systematic review was performed to determine the population that benefited from prophylactic ivermectin. Seven databases of health-related studies were searched for eligible trials without language restrictions. Randomized controlled trials (RCTs) and cohort studies investigating ivermectin for coronavirus disease 2019 (COVID-19) prevention were included. Data were pooled using a random-effects model, and subgroups were analyzed by study type and the pre-or postexposure population. The certainty of the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…In a recent meta-analysis, Marcolino et al evaluated 25 randomized clinical trials totaling over 6,000 patients and found that ivermectin does not reduce mortality risk or mechanical ventilation requirements [ 64 ]. Furthermore, a 2023 meta-analysis on the use of ivermectin for post-exposure prophylactic measures in COVID-19 management revealed that ivermectin did not exert a protective effect on this population [ 65 ]. This study by Hu et al has observed a plausible protective effect of ivermectin in preexposed populations.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis, Marcolino et al evaluated 25 randomized clinical trials totaling over 6,000 patients and found that ivermectin does not reduce mortality risk or mechanical ventilation requirements [ 64 ]. Furthermore, a 2023 meta-analysis on the use of ivermectin for post-exposure prophylactic measures in COVID-19 management revealed that ivermectin did not exert a protective effect on this population [ 65 ]. This study by Hu et al has observed a plausible protective effect of ivermectin in preexposed populations.…”
Section: Reviewmentioning
confidence: 99%
“…This study by Hu et al has observed a plausible protective effect of ivermectin in preexposed populations. However, the authors have cautioned that the results of this study should be interpreted with caution due to the poor quality of evidence in this subset of patients [ 65 ]. This suggests that further research is warranted to verify these findings and determine the potential utility of ivermectin in this context.…”
Section: Reviewmentioning
confidence: 99%
“…Gong-Yi Hu с соавт. в систематическом обзоре, включившем рандомизированные и когортные иссле- Хотя эффективность ивермектина и была продемонстрирована, результаты оказались ненадежными изза низкого качества доказательств [34].…”
Section: с января 2020 по май 2023 года ситуация с новой коронавирусн...unclassified